La producción del conocimiento a través de la educación no formal en programas sociales - Game Varas, Cinthya Isabel (2016)
Non-formal education arises from the social problems of citizen construction, which promotes an alternative education with actions that strengthen social coexistence and its development throughout life. Recognizing education as a social practice is how it is conceived within social programs, In order to favor the learning processes. Their disciplinary logic and educational policies manage the production of knowledge. This work seeks to show the demands of the globalized world, together with the needs of peaceful coexistence, which must be prepared to incorporate new models of knowledge production for the development of people; as well as their social, cultural and economic development in the countries. In this way, the new education would have the task 99of thinking and restructuring, to guarantee the transformations that it needs. By reframing learning, other perspectives would be established that will require new trends in the transfer of knowledge, to respond to the new contexts on the study of the reality. In this context, the flexibility to make strategies to reach to educational proposals for all, would be presented as an opportunity to learn. This strategy would serve as a bridge between the reintegration into knowledge and the production of knowledge, within new spaces that allow the educational continuity of the apprentices-citizens.